2023
DOI: 10.1259/bjr.20220707
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of automated personalised breast radiotherapy planning techniques with scripting in Raystation

Abstract: Objectives: Implement scripted automatic breast planning (AP) for breast techniques within Raystation. Methods: Manual plans (MP) were re-planned and compared with AP plans for whole breast (WB), partial breast (PB), hybrid VMAT SIB and VMAT nodal plans. Results: WB AP plans took 7 min comparing well to MP. One WB AP failed a mandatory dose constraint. Small statistically significant differences showed improved coverage for AP at expense of slightly hotter plans, however absolute differences were small (mean d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The MF approach is the standard breast VMAT planning technique. Previous studies reported that the MF plans were more robust than the no-flash VMAT plans for the whole breast irradiation due to the achievement of a skin flashing effect [2,31]. Figure 6 confirms that the RO could achieve a similar skin flashing effect but without any need for manual creation of pseudo skin flash, which could result in potential time saving despite not being the focus of this study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The MF approach is the standard breast VMAT planning technique. Previous studies reported that the MF plans were more robust than the no-flash VMAT plans for the whole breast irradiation due to the achievement of a skin flashing effect [2,31]. Figure 6 confirms that the RO could achieve a similar skin flashing effect but without any need for manual creation of pseudo skin flash, which could result in potential time saving despite not being the focus of this study.…”
Section: Discussionsupporting
confidence: 62%
“…The prescription was standardized to deliver 50 Gy in 25 fractions without simultaneous integrated boost. The plans were optimized using a maximum of 40 iterations per optimization cycle and the final dose was calculated using a collapsed cone [31].…”
Section: Treatment Planningmentioning
confidence: 99%
“…Another disadvantage is that the positions of the secondary field and jaw need reference objects based on the V105 dose distribution; however, a quantifiable reference target typically does not exist. Based on geometric or dosimetric means, limiting edge beams to 5-10°may help clarify the ideal angle of secondary field placement (Zhao et al 2012, Gleeson et al 2023.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the availability of scripting in some commercial treatment planning systems has further increased the ability of clinical teams to develop tools to improve their workflows. 38 , 39 The role of the RPA in this environment is likely to constantly change, as we work to help clinics that are not benefitting from these other available tools, with the long-term goal of helping to improve equality and equity in the availability of cancer treatments across the world.…”
Section: Discussionmentioning
confidence: 99%